1997
DOI: 10.1091/mbc.8.3.533
|View full text |Cite
|
Sign up to set email alerts
|

Specific release of membrane-bound annexin II and cortical cytoskeletal elements by sequestration of membrane cholesterol.

Abstract: Annexin II is an abundant protein which is present in the cytosol and on the cytoplasmic face of plasma membrane and early endosomes. It is generally believed that this association occurs via Ca2+-dependent binding to lipids, a mechanism typical for the annexin protein family. Although previous studies have shown that annexin II is involved in early endosome dynamics and organization, the precise biological role of the protein is unknown. In this study, we found that approximately 50% of the total cellular ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
164
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(177 citation statements)
references
References 60 publications
11
164
0
Order By: Relevance
“…A similar phenomenon was observed with the cytoplasmic protein annexin II, which is expressed on the surface of various cell types (36). Interestingly, cell surface-expressed moesin interacts with heparan sulfate, LPS, and components of rabies and measles viruses (8,18,19,28,37).…”
Section: Discussionsupporting
confidence: 61%
“…A similar phenomenon was observed with the cytoplasmic protein annexin II, which is expressed on the surface of various cell types (36). Interestingly, cell surface-expressed moesin interacts with heparan sulfate, LPS, and components of rabies and measles viruses (8,18,19,28,37).…”
Section: Discussionsupporting
confidence: 61%
“…Early endosomes also supported HPTS incorporation with either protocol (see Figures 5B and 6B, and Supplemental Figure S6D), as expected because the invagination process begins in early endosomes (Gruenberg and Stenmark, 2004;Piper and Katzmann, 2007). By contrast, a heavy membrane fraction recovered from the same gradient (see Figure 1A), which contained the plasma membrane and early biosynthetic membranes but not endosomes (Gu et al, 1997;Harder et al, 1997;Rojo et al, 1997), did not support HPTS incorporation with either protocol (data not shown). These observations demonstrate that HPTS was incorporated from the solution into membrane organelles, presumably late endosomes, and that this process required energy and depended on cytosolic factors.…”
Section: In Vitro Reconstitution Of Intraendosomal Buddingsupporting
confidence: 70%
“…2C and D). Reducing cell CH had no effect upon the distribution of caveolin-1 and annexin-II among these three fractions, which may be explained by the fact that both of these proteins are localized to the inner lipid leaflet of the plasma membrane where they would be less accessible to the cell impermeant MBCD [36,37]. Caveolin-1 was found predominantly in the HSP fraction containing intermediate size complexes, while annexin II was retrieved mainly in the small aggregate, HSS fraction.…”
Section: Selected Integral Tj Proteins In Tx-100 and Chaps Lysates Armentioning
confidence: 90%
“…1). The latter included: a. ZO-1, a peripheral TJ protein [35], b. caveolin-1, a membrane protein that binds CH on the inner lipid leaflet of the plasma membrane [7,36], c. annexin II, a protein that binds to acidic phospholipids in a calcium dependent manner and whose association with the plasma membrane is, in part, CH dependent [37,38], d. actin, a cytoskeletal protein linked to the TJ via cytoplasmic adaptors [39] and e. transferrin receptor a membrane protein that is reported not to be associated with DRMs [40]. The data shown are representative of those obtained from experiments that were repeated a minimum of two times, using 1 and 3.25% TX-100 or 1.2 and 4% CHAPS.…”
Section: Selected Integral Tj Proteins In Tx-100 and Chaps Lysates Armentioning
confidence: 99%